Dental arch shape and size in Malay schoolchildren with Class II malocclusion - Banabilh Saeed M.; Rajion Zainul A.; Samsudin Rani; Singh G. D. (Sciendo, 2023)
To quantify and localise differences in Class I and Class II dental arches in Malay schoolchildren.